Optimal Inﬂation and Inﬂation Targeting: International Experience - E. V. Sinelnikova-Muryleva; A. M. Grebenkina (Финансы: теория и практика)
The relationship between optimal, threshold and target inﬂation regarding the inﬂation targeting policy has been analyzed on the example of some countries. The objective of the article is to identify the features of achieving the inﬂation target by countries with different levels of economic development. As part of the descriptive analysis, the country comparison method has been applied according to the parameters of estimated inﬂation thresholds, actual targets and permissible targeting ranges, sustainability of targets and time periods. In terms of the case study approach, countryspecifc factors for changing the inﬂation target and the threshold inﬂation rate have been studied. The relationship between optimal, threshold and target inﬂation has been substantiated. The experience of achieving the inﬂation target in 17 countries in 2009–2018 has been presented. The actually targeted and estimated threshold levels of inﬂation have been compared. The article reveals the features of achieving the inﬂation target by countries with different levels of disclosure and economic development. It has been concluded that the inﬂation threshold level is the upper limit of the actually established target inﬂation rate or its range. Despite the downward trend in estimates of the threshold level, the downward trend in target inﬂation has not been pronounced. Open economy and sensitivity to changes in external conditions is a precedence factor of interest rate policy specifc to emerging market countries. As a result, the countries have to choose more ﬂexible policy, accommodative inﬂation targeting, or the policy of “leading indicators”. It is focused primarily on managing inﬂation expectations. Despite the ambiguity of the external environment, the inﬂation targeting policy in Russia retains the potential for anchoring inﬂation expectations at a chosen target level.